Perbandingan Keputusan Tata Laksana Farmakologi dan Rujukan Pasien Epilepsi Baru dengan Pasien yang Pernah Didiagnosis Sebelumnya pada Layanan Telemedik di Indonesia - Pukovisa Prawiroharjo; Yulia Puspita Dewi (PT Dexa Medica, 2025)
Introduction: Epilepsy is a condition or brain disorder characterized by a tendency for recurrent seizures. Telemedicine services use electronic communication facilities to provide medical support or care remotely. In these services, various factors influence doctors in making decisions. Objective: This study aims to compare the pharmacological management decisions and referral decisions for newly diagnosed epilepsy patients versus patients previously diagnosed by doctors in telemedicine services in Indonesia. Methods: This research uses a retrospective cross sectional design using secondary data sources from one of Indonesia's telemedicine services. A total of 100 subjects were selected within the telemedicine service. Pharmacological management decisions and referrals were assessed based on chat history. Results: Analysis of the data showed no significant difference between newly diagnosed patients and previously diagnosed in terms of pharmacological management decisions (p=0.298). However, there is a significant difference between newly diagnosed patients and previously diagnosed in terms of referral decisions (p=0.025). In addition, newly diagnosed patients appear to have a higher referral percentage (18.87%) compared to previously diagnosed patients (4.26%). Discussion: There was no significant difference in pharmacological treatment decisions between newly diagnosed patients and previously diagnosed patients. However, a significant difference was observed in referral decisions. This indicates the need for a larger sample size and further research.